Sektor usług w dobie kryzysu światowego - zmiany na rynku pracy - Węgrzyn, Grażyna (Services Sectors During the World Crisis - Changes in Labour Market, 2009)
The article puts foreword the changes within the number and the structure of working places in the Services Sectors of EU during 2000-2008 period. A recession is often defined as two successive negative quarter changes in GDP. At the end of 2008 there were significant signs of a downturn in industrial and retail sectors; some other service sectors continued to report growth. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 444-452